2021
DOI: 10.1186/s40035-021-00263-0
|View full text |Cite
|
Sign up to set email alerts
|

Dense core vesicle markers in CSF and cortical tissues of patients with Alzheimer’s disease

Abstract: Background New fluid biomarkers for Alzheimer's disease (AD) that reveal synaptic and neural network dysfunctions are needed for clinical practice and therapeutic trial design. Dense core vesicle (DCV) cargos are promising cerebrospinal fluid (CSF) indicators of synaptic failure in AD patients. However, their value as biomarkers has not yet been determined. Methods Immunoassays were performed to analyze the secretory proteins prohormone convertases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 92 publications
1
10
0
Order By: Relevance
“…Chronic neuronal inactivity also blocked DCV release and resulted in DCVs accumulation in the pre-synapse [ 73 ]. The failure in DCV release in AD is consistent with previous observation of aberrant accumulation of DCV proteins in dystrophic neurites, degenerative structures originated from axons [ 35 , 52 , 82 ] and decreased DCV proteins in the CSF as a potential biomarker for AD [ 5 ]. Because proper DCV release is important for peptidergic transmission which controls circuitry function and homeostasis [ 24 ], our finding suggests that alterations in peptidergic transmission is likely involved in AD.…”
Section: Discussionsupporting
confidence: 90%
“…Chronic neuronal inactivity also blocked DCV release and resulted in DCVs accumulation in the pre-synapse [ 73 ]. The failure in DCV release in AD is consistent with previous observation of aberrant accumulation of DCV proteins in dystrophic neurites, degenerative structures originated from axons [ 35 , 52 , 82 ] and decreased DCV proteins in the CSF as a potential biomarker for AD [ 5 ]. Because proper DCV release is important for peptidergic transmission which controls circuitry function and homeostasis [ 24 ], our finding suggests that alterations in peptidergic transmission is likely involved in AD.…”
Section: Discussionsupporting
confidence: 90%
“…In the tauopathy brain, GVBs [ 17 , 19 – 23 ] and putative GVBs [ 3 , 13 15 , 24 , 25 ] are occasionally observed in neurons without apparent tau pathology. Based on semiquantitative visual assessment, previous studies have reported a range of 5–25% [ 13 15 , 17 , 20 ] up to even 80% [ 25 ] of GVB+ neurons without pathological tau. In the current study, we performed systematic analysis of pathological tau at the single-cell level.…”
Section: Discussionmentioning
confidence: 99%
“…The strong evidence that connects tau pathology and GVBs is challenged by studies reporting the presence of GVBs [17,[19][20][21][22][23] and putative GVBs for which CK1δ positivity was not demonstrated [3, 13-15, 24, 25] in neurons lacking signal for pathological tau markers (tau−) in the human tauopathy brain. Additionally, the presence of GVBs has also been associated with α-synucleinopathies including Parkinson's disease (PD) [11,[26][27][28][29][30], PD with dementia [4,28,31] and multiple system atrophy (MSA) [4,30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we repeated the module visualization, cell-type specific differential gene expression, and SCG2, SCG3, SCG5, CHGA, and CHGB encode for neuropeptides precursors/neuropeptides secretogranin II, Secretogranin III, 7B2, chromogranin A (CGA), and chromogranin B (CGB) that will be proteolytically processed into neuropeptides in the chromogranin-secretogranin family (75). These peptides are major constituents of and often markers of dense core vesicles (DCV) that store neuropeptides (76). Our finding signifies that the disruption of NP signaling in AD is likely widespread (e.g., not limited to a couple of NPs).…”
Section: Decreased Np Cell Population In Ad Entorhinal Cortexmentioning
confidence: 99%